Potensi Gracilaria sp. dan Ulva sp. Sebagai Pakan Benih Siganus guttatus - Darsiani Darsiani; Guyanti Guyanti; Sri Redjeki Hesti Mulyaningrum; Andi Arham Atjo; Muhammad Haritza Laitte; Yanti Mutalib; Firmansyah Bin Abdul Jabbar (Jurnal Airaha, 2022)
This study aims to determine the type of seaweed that is good and can produce maximum growth and survival of Siganus guttatus. This research was carried out from June-September 2021, at at the Shrimp Hatchery Installation (IPUW), Barru, South Sulawesi. This study used a completely randomized design (CRD) used three treatments with three replications. The treatments used were treatment A (100% control of commercial feeding), treatment B (feeding Gracilaria sp. 100 %), treatment C (feeding Ulva sp.). The parameter measured were Specific Growth Rate (SGR), Absolute Growth, Survival and Palatability. The data was analyzed using Analysis of Variance (ANOVA) and with the W-Tukey test if there were differences between treatments. 180 Siganus guttatus juveniles (average weight of 5.65 g) were reared in a tanks (62x41x51 cm) for 75 days. The highest daily growth was obtained in commercial feed A (PF 1000) which was 1.53 g, the highest absolute growth was obtained in treatment A (Commercial Feed) 12.29 g, both treatments B (Gracilaria sp.) 4.30 g and the lowest was treatment C (Ulva sp.) .) 2.82 g. The highest survival rate (survival rate) was obtained in treatment A (Commercial Feed) and B (Gracilaria sp.) 98.33%, and the lowest was in treatment C (Ulva sp.) with an average value of 85.00%. Based on the results of the ANOVA test, it can be concluded that the research conducted by providing commercial feed (PF 1000), Gracilaria sp. and Ulva sp. significant effect (P<0.05) on specific growth, absolute growth, survival and palatability of baronang fish (Siganus guttatus). The results showed that the highest feed consumption value was in treatment A of 144.57 g, followed by Treatment B (Gracilaria sp.) of 142.19 g and the lowest of treatment C (Ulva sp.) of 100.01 g.